Case report: Histopathological Diagnosis of Rabies in Iraqi Cows and Ewes: Magda Saeed Abdullah ,Thaer Abdul Karim Ansif ,Amin Ali Odeh - Abdullah, Magda Saeed (The Iraqi Journal of Veterinary Medicine, 2011)
Rabies was diagnosed (for the first time) in clinically suspected rabid Iraqi cows and ewes by using histopathological methods. The result showed 3 positive cases 2 cows from Baghdad governorate and 1 ewe from Al - Basra governorate. The gross pathological changes included swelling of cerebrum and cerebellum, multiple hemorrhagic spots within cerebral parenchyma, and sever congestion in meningial blood vessels. The histopathological changes showed specific changes represented by Negri bodies as intracytoplasmic inclusions within Purkinje cells in cerebellum and Babes nodules in cerebrum and medulla oblongata. Non specific changes included edema, hemorrhages, cellular necrosis, lymphocytic foci and lymphocytic and mononuclear cuffing surrounding congested blood vessels.